Análisis de atrayentes para la mosca de la fruta y su incidencia en la estacionalidad. - Espinosa Cunuhay, Kleber Augusto (2020)
The research was carried out in the sectors of Palmar, California, Oriente, in the Tingo la Esperanza parish of the Pujilí canton, Cotopaxi Province, where the main problem is the management of the fruit fly of the genus Anastrepha sp, the same that has reduced the production of fruit trees in the area, which is why the analysis of seasonality and the influence of attractants in Anastrephasp was proposed as a general objective. In fruit trees, using as a methodology a DBCA design with a factorial arrangement of 4x2 with three repetitions, where four attractants and two doses were used, for the realization of seasonality and the influence of environmental factors, the same Hargreaves formulas were taken into account In a map indicating the fluctuation of the climatic factors, for the analysis of the number of flies captured per day the MTD formula was used, whose results of the investigation were that the three most frequent species in the study area were A. fraterculos, A. striata and A. spp, as well as the most effective attractant was cane honey in low doses of 100 cc / l, while the percentages with the highest capture was the species A. fratercles that had the highest percentage with 52.16%, it has a 0.027MTD and the months with the highest catch were in March and June, the same ones that determined the influence of climatic factors on the behavior of the fruit fly. .